The control of genetic parameters on grain yield and its components in hexaploid wheat - N. K. Yousif; H. A. Abass (Tikrit Journal of Pure Science)
Controlling of genetical parameters on grain yield and its components were study in six generation (P1,P2,F1,F2,B1 and B2) for two crosses of hexaploid wheat, Triticum aestivum L. (Iba-99 x Reyna-27) and (Abochareeb-3 x Jawaher-20) to estimate: gene action parameters, components of genetic variance, environmental variance, average degree of dominance, broad sense heritability, narrow sense heritability and expected genetic advance from selection in F2. Two models were applied in analyzing the component of generation means and the total phenotypic variance for studied traits in six generations for each cross were analyzed. The results showed that: The three parameter genetics models were adequate for the inheritance of spike number and grain yield in tow crosses and there were significant additive, dominance and epistatic effects on the other traits. Over dominance for studied traits, but partial for 100 grain weight in the first cross, plant height and spike length in the second cross. Narrow sense heritability and expected genetic advance were high for most traits.